The Impacts of Students' Reading Habit and Their Language Attitudes toward Reading Comprehension - Novari, Ari Fajria (Journal of English Education Studies, 2018)
This research is aimed as follows: to get empirical data and analyze the impacts of reading habit and language attitudes towards students’ reading comprehension at private Senior High School in Pandeglang, Banten Province. This research is done by statistics, Kolmogorov-Smirnov test, to test the normality, and Anova Table. The research was held at Private Senior High School in Pandeglang. Data was collected by giving instruments for reading habit (questionnaire/16 items), language attitude (questionnaire/16 items) to eleven grade students at Madrsasah Aliyah Mathla’ul Anwar, MAN 1 Pandeglang, and SMA Mathla’ul Anwar Menes. Due to the result, it can be inferred that there is an impact of reading habit towards students’ reading comprehension (Sig.=0.000 and t_test=14.648; while t_(table=) 1.669). There is an impact of language attitude towards students’ reading comprehension (Sig.=0.040 and t_test=0.846; while t_(table=) 1.669). There are impacts of reading habit and language attitudes toward students’ reading comprehension, the score of Sig. = 0.000 < 0.05 and F_test =160.024; while F_table=3.148, so Ho is rejected, it means that the regression coefficient is significant.